La Conversation des sexes: philosophie du consentement - Garcia, Manon (Climats, 2021)
« L'affaire Weinstein et le mouvement #MeToo ont mis la question des violences sexuelles au premier plan. Depuis, le consentement renvoie naturellement au consentement sexuel et amoureux, envisagé comme un sésame de l'égalité entre femmes et hommes. Pourtant, il est bien difficile à définir, et soulève trois problèmes. Le problème juridique, bien connu de celles et ceux qui suivent l'actualité, peut être résumé ainsi : que faire pour que les cas de viol, d'agression et de harcèlement sexuels soient efficacement punis? Le deuxième problème est moral : comment penser des relations amoureuses et sexuelles qui ne soient pas fondées sur des normes sociales sexistes et inégalitaires? Enfin, le problème politique : comment ne pas reconduire les injustices de genre qui se manifestent dans les rapports amoureux et sexuels? La magistrale analyse du consentement que propose Manon Garcia revisite notre héritage philosophique, plongeant au cœur de la tradition libérale, mettant à nu ses impensés et ses limites. De John Locke aux théoriciennes féministes françaises et américaines, en passant par Michel Foucault et les débats sur la pratique du BDSM, c'est une nouvelle cartographie politique de nos vies privées que dessine cet essai novateur. Au terme de ce livre, il s'agira en somme, pour reprendre la formule de Gloria Steinem, d'« érotiser l'égalité » plutôt que la domination : en ce sens, le consentement sexuel, conçu comme conversation érotique, est sans doute l'avenir de l'amour et du sexe. »
Section: 308 pages ; 21 cm
Keywords: 2000 à aujourd'hui; approches et analyses; consentement; cours; discipline; droits des femmes*; europe; france; féminisme pop; justice sociale; metoo; phi4336; philosophie; premier cycle; périodes historiques; relations amoureuses; régions géographiques; sciences humaines; sexualité; thématiques

Pornography embodied: from speech to sexual practice - Mason-Grant, Joan (Rowman & Littlefield, 2004)
What does it mean to conceptualize pornography as a material practice rather than as speech? Mason-Grant argues that this idea, fundamental to the work of Andrea Dworkin and Catharine MacKinnon, has been obscured in legal wrangling and political polarization over their civil ordinance. Within the arena of legal argument, where the principle of free speech holds sway for progressive thinkers, their analysis of pornography is rendered, at worse, an apology for censorship and, at best, an argument about the social force of speech, rather than recognized as a fundamental challenge to the very idea of pornography as speech. In this book, Mason-Grant first shows how the persistent 'speech paradigm' inevitably obscures the innovative core of the Dworkin-MacKinnon critique of mainstream pornography. She then develops an alternative 'practice paradigm' that critically engages their analysis, capturing and extending its core insights about the role of pornography in sexual practice. Drawing on phenomenology of the lived body, this alternative paradigm provides a way of re-thinking how the pervasive use of mass-market heterosexual pornography contributes to the cultivation of an embodied and tacit sexual know-how that is subordinating, and raises important questions about alternative materials produced and used by sexual minorities. In her conclusion, Mason-Grant considers the implications of her analysis not for law, but for a critical pedagogy in youth sexuality education.
Section: x, 193 pages
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme pop; hétérosexisme; militance; patriarcat; philosophie; phénoménologie; premier cycle; pédagogie; sciences humaines; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists – including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan – whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

Feminism and postmodernism - Ferguson, Margaret; Wicke, Jennifer (Duke University Press, 1994)
This collection of essays explores the significant agreements and tensions between contemporary feminist and postmodern theories and practices. Having brought enormous changes to conceptions of the body, identity, and the media, postmodernity compels the rethinking of many feminist categories, including female experience, the self, and the notion that "the personal is political." Feminist analysis has been equally important, though not always equally acknowledged, as a force within postmodernism. Feminist writings on subjectivity, master narratives, and the socioeconomic underpinnings of the master narrative of theory itself have been particularly influential. This volume traces the crossings and mutual interrogations of these two traditions into the arenas of cultural production, legal discourse, and philosophical thought. Multidisciplinary and international in their collective focus, the essays range from a study of Madonna as an Italian American woman who is revising the cultural meanings of an ethnic feminism to a unique interview with Mairead Keane, the national head of the Women’s Department of the Irish political party Sinn Fein. Turning the prism of postmodern feminism onto such diverse cultural objects as literary and literary critical texts, contemporary film, and music, these essays intervene in debates regarding technology, sexuality, and politics. Challenging modern feminisms to articulate their inescapable relation to postmodern society, this expanded edition of a special issue of boundary 2 also explores ways in which feminism can work as the cutting edge of a global postmodernism. Contributors. Salwa Bakr, Claire Detels, Margaret Ferguson, Carla Freccero, Marjorie Garber, Barbara Harlow, Laura E. Lyons, Anne McClintock, Toril Moi, Linda Nicholson, Mary Poovey, Andrew Ross, David Simpson, Kathyrn Bond Stockton, Jennifer Wicke
Keywords: amériques; approches et analyses; cours; discipline; fem1000; féminisme pop; irlande; philosophie; postmodernisme; premier cycle; régions géographiques; sciences humaines; troisième vague; états-unis; études culturelles

Unmarked: the politics of performance - Phelan, Peggy (Routledge, 1993)
Feminist film theory has made the psychic and political limitations of representational visibility abundantly clear. Yet the Left continues to promote visibility politics as a crucial aspect of progressive struggle. Unmarked examines the fraught relation between political and representational visibility and invisibility within both mainstream and avant-garde art. Suggesting that there may be some political power in an active disappearance from the visual field, Phelan looks carefully at examples of such absences in photography, film, theatre, the iconography of anti-abortion demonstrations, and performance art. A boldly specultative analysis of contemporary culture, Unmarked is a controversial study of the politics of performance. Situating performance theory within emerging theories of psychoanalysis, feminism, and cultural studies, Phelan argues that the non-reproductive power of performance offers a different way of thinking about cultural production and reproduction more generally. Written from and for the Left, Phelan's readings of the work of Robert Mapplethorpe, Cindy Sherman, Mira Schor, Yvonne Rainer, Jennie Livingstone, Tom Stoppard, Angelika Festa and Operation Rescue radically rethink the politics of cultural representation.
Keywords: amériques; approches et analyses; arts; cours; discipline; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; philosophie; premier cycle; psychanalyse; ressource en ligne; régions géographiques; sciences; sciences humaines; sex2283; thématiques; états-unis